The princess diaries sixsational - Cabot, Meg (Macmillan London, 2007)
Student body president, that is--nominated by her power-mad best friend, Lilly. This is not how Mia imagined kicking off her sophomore year, but as usual, she has bigger problems to worry about, like Geometry. And now that Mia's one true love, Michael, is uptown at college, what's the point of even getting up for school in the morning? But the last straw is what Lana whispers to her on the lunch line about what college boys expect of their girlfriends. . . . Really, it's almost more than a princess in training can bear!